2007
DOI: 10.1099/vir.0.82335-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recombination in turnip mosaic virus genomic sequences indicate hotspots of recombination

Abstract: Potyviruses have variable single-stranded RNA genomes and many show clear evidence of recombination. This report studied the distribution of recombination sites in the genomes of 92 isolates of the potyvirus Turnip mosaic virus (TuMV); 42 came from the international gene sequence databases and an additional 50 complete genomic sequences were generated from field samples collected in Europe and Asia. The sequences were examined for evidence of recombination using seven different sequence comparison methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(129 citation statements)
references
References 70 publications
12
115
1
1
Order By: Relevance
“…The phylogenetic groups of the isolates, namely IRN-1 and IRN-2, closely corresponded to the L and N biological groups, respectively ( Table 2). These data seem to indicate the important role of "host" in the evolution of TYFRV populations, as reported previously for other viruses (Ohshima et al, 2007). The amino acid sequence comparison of nucleoprotein genes of the isolates between the two groups showed 90.8−92.7% identities, which are close to the threshold value used for species determination in the genus Tospovirus (90.0%) (Goldbach and Kuo, 1996).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The phylogenetic groups of the isolates, namely IRN-1 and IRN-2, closely corresponded to the L and N biological groups, respectively ( Table 2). These data seem to indicate the important role of "host" in the evolution of TYFRV populations, as reported previously for other viruses (Ohshima et al, 2007). The amino acid sequence comparison of nucleoprotein genes of the isolates between the two groups showed 90.8−92.7% identities, which are close to the threshold value used for species determination in the genus Tospovirus (90.0%) (Goldbach and Kuo, 1996).…”
Section: Discussionsupporting
confidence: 60%
“…Recombination plays a pivotal role in diversification and evolution of both plant RNA and DNA viruses (Ohshima et al, 2007;Prasanna and Rai, 2007). In this study, none of the TYFRV isolates seemed to be recombinants.…”
Section: Discussionmentioning
confidence: 82%
“…More results have been reported that the recombination events occurred throughout the HC-Pro gene of SCSMV but not in the P1 gene (Bagyalakshmi et al, 2012;He et al, 2013). Recombination events have been reported as the evolutionary history of single-stranded RNA genome such as Turnip mosaic virus (TuMV), in the P1, HC-Pro, P3, CI, 6K2, VPg, NIa-Pro, NIb and CP genes, except for 6K1 gene (Ohshima et al, 2007). The recombinant isolate (GK76-4) obtained in this study was found to have two recombination sites which occurred in the variable N-terminal region and the conserved sequence at the C-terminal regions of the CP gene (Table 4).…”
Section: Discussionmentioning
confidence: 97%
“…However, any regions of homology are usually short and may be associated with secondary structures that facilitate the recombination process . Some of the typical properties of sites involved in recombination between viral RNAs include an AU-rich sequence adjacent to a 5' GC-rich region Ohshima et al, 2007;Vives et al, 2005).…”
Section: Incorporation Of Donor Genetic Materialsmentioning
confidence: 99%